Enhancement of antioxidant activity by the combination of moringa oleifera and perilla frutescens seed oils in microemulsion - Prakairat Tunit (2020)
© 2020 Trans Tech Publications Ltd, Switzerland. The aim of this study was to investigate the enhanced antioxidant activity of microemulsion containing mixed Moringa oleifera seed oil and Perilla frutescens seed oils, compared with microemulsion of single oils. The novel microemulsions for the moringa, perilla, and mixed seed oils were formulated by mixing appropriate amount of surfactant, water, and oil phase. The formulation containing the maximum amount of oil which appeared transparent was further evaluated for particle size, size distribution, surface charge, pH, and rheological behavior. The in vitro antioxidant properties of microemulsions were investigated in comparison with essential oils. Cream containing microemulsion was prepared and its physical stability was investigated by heating-cooling cycles. The results showed that the maximum content of oil incorporated in microemulsion system was 12.5%. The mean droplet sizes of moringa, perilla, and mixed oil microemulsion were 159.33±0.77, 183.86±1.42, and 263.43± 9.40 nm, respectively. All formulations exhibited pseudoplastic flow behavior. The mixture of moringa and perila seed oils in microemulsion possessed the highest significant antioxidant effect against 1,1-diphenyl-2-picrylhydrazyl compared with single oil microemulsion. The cream containing microemulsion exhibited good physical stability. Thus, the current research reveals the benefits of microemulsion containing mixed moringa and perilla seed oils based cream compared with single essential oils.